The Influence of Promotion Content at Shopee Indonesia’s Instagram Account on Consumptive Behaviour for Late Adolescent Girls in Jakarta - Reni Dyanasari; Silvialestari, Dewi; Syifa Mutma, Faisya (LSPR Institute of Communication & Business, 2024)
The rise in online shopping in Indonesia is significantly linked to National Online Shopping Day (Harbolnas), launched on December 12, 2012, by the Indonesian E-commerce Association (idEA). Harbolnas has become essential for both sellers and buyers, with the “8.8” August 2020 promotion alone increasing transactions by 66%. Monthly twin date promotions by platforms like Shopee Indonesia drive consumer engagement. Instagram plays a key role in influencing late adolescent girls' shopping behavior in Jakarta. For that, this study wanted to see how the impact of promotional content on Instagram accounts @shopee.id on late adolescent consumptive behavior of girl in Jakarta. This study uses a post-positivist paradigm with quantitative methods, collecting data through surveys targeting this demographic. The correlation table results indicate that the content has an influence on consumptive behavior, as the obtained value is 0.544, which falls into the category of moderately correlated. Furthermore, based on the coefficient of determination formula, the contribution of the content variable (X) to consumptive behavior (Y) is found to be 29%, while the remaining 71% is influenced by other factors outside the variables in this study. In this study, the linear regression equation can be observed as Y = 14059 + 0.800 (11) = 14067.8. This indicates that in this study, the value of consumptive behavior will increase as the value of promotion content increases.